IDENTIFICAÇÃO DOS STAKEHOLDERS ENVOLVIDOS NO PROCESSO DE DESENVOLVIMENTO DE PROJETOS NA CADEIA DA CONSTRUÇÃO CIVIL DO ESTADO DO CEARÁ: O PRIMEIRO PASSO PARA ADOÇÃO DO BIM - Böes, Jeferson Spiering; Lima, Mariana Monteiro Xavier de; Barros Neto, José de Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The adopting Building Information Modeling (BIM) within a production chain requires macro insight. The challenges are numerous as they encompass a range of stakeholders, each with its numerous project development methodologies, specifications and customer requirements. The present work is based on the actions adopted by SINDUSCON-CE, not qualified in 2016, its strategic planning for the implementation of BIM in the civil construction production chain of the state of Ceará. The first step, the creation of a working group (GT-BIM), identified the stakeholders involved in the process of developing the construction works linked to INOVACON (Innovation in Civil Construction Program), the technological arm of SINDUSCON. -CE. In total, 18 construction companies were interviewed, identifying 24 stakeholders and totaling 165 stakeholders. The following GT-BIM steps are: (i) Characterization of current BIM data in the state of Ceará; (ii) Measurement of BIM maturity in the civil construction productive chain; (iii) To propose a strategic implementation methodology for BIM in the civil construction chain of Ceará.